A Novel Technique for Shortening Orthodontic Treatment: The “JET System” - Shinichi Narita; Kiyoko Narita; Masaru Yamaguchi (Medicina, 2022)
We have developed a novel technique, the Jiyugaoka Enjoyable Treatment (JET) system, to complete orthodontic treatment in a short time. It entails the use of the regional acceleratory phenomenon (RAP), light continuous forces and low friction in cases involving extraction. In the JET system, tooth extraction not only creates space, but also triggers the RAP; thus tooth extraction accelerates orthodontic treatment. We describe for the first time how to use the JET system to shorten treatment time in a patient in whom four premolars were extracted. A 15 year old girl patient exhibited an Angle Class I bimaxillary protrusion with moderate crowding in the maxillary (−5.0 mm) and mandibular arches (−3.5 mm). Her facial appearance was slightly asymmetric, and her facial profile was convex. Immediately after the simultaneous extraction of the maxillary first premolars and mandibular second premolars, orthodontic treatment was started with a combination of passive self-ligating brackets and super-elastic nickel-titanium closed coil springs that provided orthodontic forces of less than 50 gf (1.8 ozf). The appliance was adjusted once a month. The total treatment time was 13 months. Cephalometric superimpositions showed a slight anchorage loss, and panoramic radiographs showed a slight apical root resorption but no significant reduction in the crest bone height. At the 3-year 6-month retention follow-up, stability was excellent. The JET system might shorten the orthodontic treatment period without serious anchorage loss or other adverse effects.